2018
DOI: 10.1038/s41598-018-35342-2
|View full text |Cite
|
Sign up to set email alerts
|

Spent embryo culture medium metabolites are related to the in vitro attachment ability of blastocysts

Abstract: The metabolomic profile of an embryo culture medium can aid in the advanced prediction of embryonic developmental potential and genetic integrity. But it is not known if this technology can be used to determine the in vitro potential of inner cell mass (ICM) in adherence and proliferation. Here, we investigated the developmental potential of mouse 2-cell embryos carrying cisplatin-induced DNA lesions (IDL), beyond blastocyst stage using ICM outgrowth assay. The genetic integrity of ICM cells was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Ability of the blastocyst to attach and proliferate post-implantation in vitro was assessed using ICM outgrowth assay. In vitro derived blastocysts appearing morphologically normal with expanded blastocoel at 120 hour-post insemination (hpi) were selected for ICM outgrowth assay [21,22]. Briefly, multi-well dishes (D7039, Sigma Aldrich, USA) were pre-coated with gelatin (0.1%) for 30 min at room temperature.…”
Section: Inner Cell Mass (Icm) Outgrowth Assaymentioning
confidence: 99%
“…Ability of the blastocyst to attach and proliferate post-implantation in vitro was assessed using ICM outgrowth assay. In vitro derived blastocysts appearing morphologically normal with expanded blastocoel at 120 hour-post insemination (hpi) were selected for ICM outgrowth assay [21,22]. Briefly, multi-well dishes (D7039, Sigma Aldrich, USA) were pre-coated with gelatin (0.1%) for 30 min at room temperature.…”
Section: Inner Cell Mass (Icm) Outgrowth Assaymentioning
confidence: 99%
“…The regulation of blastocyst development and outgrowth adhesion independently of gene activation enables cells to adapt to alter-ations in the conditions of in vitro culture. It was recently suggested that spent embryo culture medium metabolites might be related to the ability of blastocysts to undergo outgrowth [58]. In a metabolite analysis of embryo culture medium, non-outgrowth blastocysts that lacked the ability to adhere in vitro had increased requirements for lactate and pyruvate, and showed a significant reduction of the pyruvate-alanine ratio.…”
Section: Resultsmentioning
confidence: 99%
“…In a metabolite analysis of embryo culture medium, non-outgrowth blastocysts that lacked the ability to adhere in vitro had increased requirements for lactate and pyruvate, and showed a significant reduction of the pyruvate-alanine ratio. Thus, it was proposed that the aforementioned metabolites from the spent medium should be further analyzed using proper experimental models to substantiate their potential as biomarkers for predicting the implantation competence of embryos in clinical IVF-ET programs [58].…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the energy metabolism during early embryonic development, energy consumption is relatively low until pre-compaction stage and the main source of ATP is derived from pyruvate through oxidative phosphorylation, whereas with blastocyst formation and cavitation process a significant increase on energy demand and consumption of glucose, pyruvate and oxygen are expected. Additionally, after formation of the blastocyst, other sources of energy are required in greater proportion, including: glucose, amino acids and lipids (D'Souza et al, 2018;Hu and Yu, 2017).…”
Section: Lipids and Other Determining Molecules For Embryo Competencementioning
confidence: 99%